Enterococcus faecium as a Salmonella surrogate in the thermal processing of wheat flour: Influence of water activity at high temperatures. (September 2018) - Liu, Shuxiang; Rojas, Rossana V.; Gray, Peter; Zhu, Mei-Jun; Tang, Juming
Abstract: This study investigated the influence of temperature-dependent water activity (aw ) on thermal resistances of Enterococcus faecium NRRL B-2354 ( E. faecium ) and Salmonella Enteritidis PT 30 ( S. Enteritidis) in wheat flour. The aw for wheat flour samples at 20, 40, and 60 °C was determined by a vapor sorption analyzer and at 75, 80 and 85 °C using custom-built thermal cells with high temperature humidity sensors. Full-factorial isothermal inactivation studies of both strains in sealed aluminum-test-cells included three temperatures (75, 80, and 85 °C) and three aw, 25°C levels (0.30, 0.45 and 0.60 within ±0.02 range, prior to the thermal treatments). Isotherm results of wheat flour demonstrate a significant increase (P < 0.05) of aw as temperature rises (e.g. aw, 25°C = 0.45 ± 0.02 became aw, 80°C = 0.71 ± 0.02 in a closed system). Inactivation kinetics of both microorganisms fitted a log-linear model, the yielded D-values varied from 2.7 ± 0.2 min (D85°C of S. Enteritidis at aw, 25°C 0.60 ± 0.02) to 65.8 ± 2.5 min (D75°C of E. faecium at aw, 25°C 0.30 ± 0.02). The zT of E. faecium and S. Enteritidis decreased from 16.4 and 16.9 °C, respectively, to 10.2 °C with increased moisture content (dry basis) from 10 to 14%. Under all tested conditions, E. faecium exhibited equal or higher (1.0–3.1 times) D- and zT -values than those of Salmonella . Overall, E. faecium should be a conservative surrogate for Salmonella in thermal processing of wheat flour for control of Salmonella over a moisture content of 10–14% and treatment temperatures between 75 and 85 °C. Highlights: Water sorption isotherms of wheat flour at 20, 40, 60, and 80 °C are provided. At fixed moisture content, water activity of wheat flour increased as temperature rose from 25 to 80 °C. Reduced water activity increased D-and zT -values of Salmonella and E. faecium in wheat flour. E. faecium appears to be a valid surrogate for thermal inactivation of Salmonella in wheat flour.